Serinicoccus sediminis sp. nov., isolated from tidal flat sediment. Issue 7 (3rd May 2019) - Lee, Dong Wan; Yoo, Yeonjae; Lee, Hanbyul; Kwon, Bong-Oh; Khim, Jong Seong; Yim, Un Hyuk; Kim, Beom Seok; Kim, Gyu-Hyeok; Kim, Jae-Jin
Abstract : A novel Gram-strain-positive, non-spore-forming bacterial strain, designated GP-T3-3 T, was isolated from sediment sampled at a tidal flat in Gopado, Republic of Korea. Cells were aerobic, catalase-negative, oxidase-positive, non-motile cocci that occurred singly, in pairs or in clusters. Strain GP-T3-3 T grew at 4–45 °C (optimum, 28–37 °C), at pH 4.0–12.0 (pH 8.0–9.0) and in the presence of 0–15 % (w/v) NaCl (3–5 %). Colonies of strain GP-T3-3 T were deep-yellow, circular, smooth and pulvinate. The results of the phylogenetic analyses based on 16S rRNA gene sequences indicated that strain GP-T3-3 T was closely related to Serinicoccus profundi MCCC 1A05965 T (99.1 %), Serinicoccus chungangensis CAU 9536 T (99.0 %) and Serinicoccus marinus JC1078 T (98.0 %). The diagnostic diamino acid in the cell-wall peptidoglycan was meso -diaminopimelic acid. The predominant respiratory quinone was MK-8(H4 ) and the major fatty acids were anteiso-C17 : 0, iso-C16 : 0, iso-C15 : 0 and anteiso-C15 : 0 . The polar lipid profile consisted of diphosphadidylglycerol, phosphadidylglycerol, phosphatidylcholine, phosphatidylinositol and two unidentified phospholipids. The DNA G+C content was 72.9 mol%. DNA–DNA relatedness values between strain GP-T3-3 T and type strains of the genus Serinicoccus ranged from 28.9 to 50.5 %. On the basis of the phenotypic differences and DNA–DNA relatedness data, the isolate represents a new species of the genus Serinicoccus, for which the name Serinicoccus sediminis sp. nov. is proposed. The type strain is GP-T3-3 T (=KCTC 49173 T =JCM 32825 T =KCCM 43309 T =KACC 19850 T ).